Squalamine and trodusquemine: two natural products for neurodegenerative diseases, from physical chemistry to the clinic. Issue 4 (26th October 2021) - Limbocker, Ryan; Errico, Silvia; Barbut, Denise; Knowles, Tuomas P. J.; Vendruscolo, Michele; Chiti, Fabrizio; Zasloff, Michael
Abstract : The natural products squalamine and trodusquemine are promising potential therapeutics against Alzheimer's, Parkinson's, and other neurodegenerative diseases for their ability to modulate protein aggregation processes and target protein misfolded oligomers that are toxic to neurons. Abstract : Covering: 1993 to 2021 (mainly 2017–2021) Alzheimer's and Parkinson's diseases are neurodegenerative conditions affecting over 50 million people worldwide. Since these disorders are still largely intractable pharmacologically, discovering effective treatments is of great urgency and importance. These conditions are characteristically associated with the aberrant deposition of proteinaceous aggregates in the brain, and with the formation of metastable intermediates known as protein misfolded oligomers that play a central role in their aetiology. In this Highlight article, we review the evidence at the physicochemical, cellular, animal model and clinical levels on how the natural products squalamine and trodusquemine offer promising opportunities for chronic treatments for these progressive conditions by preventing both the formation of neurotoxic oligomers and their interaction with cell membranes.